CURRENT CONCEPTS IN CYSTITIS: EPIDEMIOLOGY, PATHOGENESIS, AND CONTEMPORARY MANAGEMENT - Kamoljonova Go’zaloy Odiljon qizi (TADQIQOTLAR, 2025)
Abstract. Cystitis—the inflammation of the urinary bladder—remains one of the  most  common  bacterial  infections  worldwide.  Acute  uncomplicated  cystitis  is usually caused by Escherichia coli, whereas complicated and recurrent forms involve a broader range of uropathogens and host factors. Recent guideline updates emphasise rising  antimicrobial  resistance,  the  need  for  antibiotic-sparing  strategies,  and individualised prevention. This three-page review synthesises the latest evidence on epidemiology,  pathophysiology,  clinical  presentation,  diagnostic  criteria,  and evidence-based  treatment  options,  drawing  on  the  2024  European  Association  of Urology  (EAU)  and  2024  Infectious  Diseases  Society  of  America  (IDSA) recommendations.  Early  recognition,  appropriate  antimicrobial  stewardship,  and patient-centred preventive measures are critical to reducing morbidity and healthcare costs associated with cystitis.